Quantum Key Distribution (QKD) as a Wireless Telecommunications Security Solution - Devi Rahmayanti (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this research is to analyze and explore quantum theorems as a wireless telecommunications security solution in the future. This study uses a quantitative approach through simulation and performance analysis of QKD systems in wireless channels, by combining literature studies and comparative analysis between QKD and PQC. Meanwhile, the wireless communication simulation model, using the QKD protocol and PQC algorithm, with Free Space Optics (FSO), WiFi, and LiFi-based network scenarios. The simulation was carried out using MATLAB. This study is based on QKD, which uses BB84 and CV-QKD protocols on FSO 100m and LiFi wireless channels. And based on PQC, which uses the Kyber algorithm, with AES authentication for communication. Both models were simulated and tested based on the parameters of Quantum Bit Error Rate, Key Generation Rate, latency, and resistance to third-party attacks (wiretapping detection). Furthermore, the analysis was carried out quantitatively and comparatively to compare the performance of QKD and PQC based on the QBER, latency, KGR, and wiretapping detection of implementation. This analysis are combined with data based on the literature, to formulate optimal implementation strategies in the context of future wireless networks. The results indicate that QKD, specifically CV-QKD, has significant potential for use in attack-sensitive wireless communications, such as military, government, and industrial applications. However, this model requires more complex hardware and infrastructure investments in its implementation. Meanwhile, PQC offers a more ready-to-use and cost-effective solution for everyday communications that remains resilient to quantum attacks.